KEPEMIMPINAN DALAM PASANG RI KAJANG: PERSPEKTIF LIVING HADIS - Shadra, Yasser Mulla; Yeri, Yeri; Amin, Muhammadiyah; Tasbih, Tasbih; Alamshah, Anisah binti (Living Islam: Journal of Islamic Discourses, 2024)
This research attempts to identify and describe the concept of leadership from the perspective of Hadith in general and the concept of leadership from the perspective of Pasang ri Kajang. The reference of this research problem leads to how the concept of leadership according to the Prophet's Hadith, how the concept of leadership in Pasang ri Kajang, and how the encounter of leadership values between the two as a manifestation that the Kajang indigenous community is very intimate with Islamic cultural values. This research uses a mixed method that is library and field by using the concept of Edmund Husserl's phenomenology in looking at the social situation in the Kajang indigenous community. The results of this study found that Leadership in the perspective of the Prophet's hadith and Pasang ri Kajang Perspective has differences and similarities in value, ideal leadership criteria based on the Prophet's hadith. at least fulfills 5 elements, namely a leader has a leadership spirit such as the soul of the Quraysh tribe, intellectual and professional, and able to carry out the task. While leadership criteria according to Pasang ri Kajang Leadership perspective of Pasang ri kajang refers to three main aspects, namely, Macca na Lambusu (intellectual and trustworthy), Barani na gattang (brave and firm), and Sabbara na pesona (patient and trustworthy). The encounter between the two values can be seen from the aspect of intellectual and trustworthy leader criteria, besides that on the other hand the leader must also be honest, have faith in Allah Swt and be responsible. Keywords: Leadership, Hadis, Pasang ri Kajang   Penelitian ini berikhtiar mengidentifikasi dan menguraikan konsep kepemimpinan perspektif Hadis secara umum dan konsep kepemimpinan perspektif Pasang ri Kajang. Adapun rujukan permasalah penelitian ini mengarah kepada bagaimana konsep kepemimpinan menurut hadis Nabi, bagaimana konsep kepemimpinan dalam Pasang ri Kajang, dan bagaiman perjumpaan nilai-nilai kepemimpinan diantara keduanya sebagai wujud bahwa komunitas adat Kajang sangat intim dengan nilai-nilai kebudayaan Islam. Penelitian ini menggunakan metode mix method yaitu pustaka dan lapangan dengan memanfaatkan konsep fenomenologi Edmund Husserl dalam meliht situasi social pada masyrakat adat Kajang.  Hasil penelitian ini menemukan bahwa Kepemimpinan dalam perspektif hadis Nabi dan Perspektif Pasang ri Kajang memiliki perbedaan dan kesamaan nilai, kriteria kepemimpinan yang ideal berdasarkan hadis-hadis Nabi saw. paling tidak memenuhi 5 unsur, yaitu seorang pemimpin memiliki jiwa kepemimpinan seperti jiwa suku Quraisy, intelektual dan professional, serta mampu melaksanakan tugas. Sedangkan kriteria kepemimpinan menurut Pasang ri Kajang Kepemimpinan perspektif Pasang ri kajang mengacu pada tiga aspek pokok yaitu, Macca na Lambusu (intelektual dan Amanah), Barani na gattang (berani dan tegas), dan Sabbara na pesona (sabar dan tawakal). Perjumpaan nilai keduanya dapat ditinjau dari aspek kriteria pemimpin yang intelektual dan amanah, selain itu disisi lain pemimpin juga harus jujur, bertakawwal kepada Allah Swt serta bertanggungjawab. Kata Kunci: Kepemimpinan, Hadis, Pasang ri Kajang